2015
DOI: 10.1111/ans.13174
|View full text |Cite
|
Sign up to set email alerts
|

Staged venous thromboemolic events prophylaxis with low‐molecular‐weight heparin followed by aspirin is safe and effective after arthroplasty

Abstract: Staged chemoprophylaxis using LMWH followed by aspirin is a safe and effective thromboprophylactic regime that is associated with a very low rate of fatal PE and all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Others reported a very low rate of DVT (0.1%) and no PE in a series of 828 patients (1000 UKA) [4]. However, several studies have noted lethal PE after UKA 0.07% [5] and 0.6% [9] and 0.96% with single stage bilateral UKA [5]. All but one of these series utilized chemoprophylaxis and early mobilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others reported a very low rate of DVT (0.1%) and no PE in a series of 828 patients (1000 UKA) [4]. However, several studies have noted lethal PE after UKA 0.07% [5] and 0.6% [9] and 0.96% with single stage bilateral UKA [5]. All but one of these series utilized chemoprophylaxis and early mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…The operation is of smaller magnitude than TKA based upon the amount of bone preparation and blood loss, presumably triggering less metabolic injury. However, tourniquet times are similar for UKA and TKA, which has raised the debate as to whether the two procedures carry the same thromboembolic risk [5, 6]. A number of studies have been published demonstrating the risk of deep vein thrombosis (DVT)/pulmonary embolism (PE) to be lower with UKA [6, 7] whereas others have noted a similar risk of PE or death from PE [5, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Data on thromboembolic complications in reconstructive microsurgery are sparse, but a previous study on microsurgical breast reconstructions reported a slightly higher thromboembolic complication rate of 2.2% [30]. Thromboembolic complications are more common in orthopaedic surgery, with figures ranging from 2.5%-18%, despite the use of low-molecularweight heparin [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Asopa et al 19 looked at 9,035 patients undergoing hip and knee arthroplasty; investigating the VTE rate of its current protocol. Those deemed high risk were given 20 mg LWMH twice a day until discharge and then aspirin 300 mg once daily.…”
Section: Resultsmentioning
confidence: 99%
“… 4 Of the eight studies looked at in this report, a DVT rate of 0.66% was found with five of them backing aspirin as prophylaxis for VTE after orthopedic surgery 15 16 17 18 21 and the other three showing promising results. 19 20 22 It is surprising therefore that NICE still do not recommend aspirin as VTE prophylaxis after major lower limb orthopedic surgery. 8…”
Section: Discussionmentioning
confidence: 99%